SISTEM KONTROL KEMUDI KAPAL BERBASIS SCADA MENGGUNAKAN APLIKASIH CX PROGRAMMER DAN EASYBUILDER - Aji, Bambang Laksono; Susilo, Kunto Eko (STMIK Palangkaraya, 2021)
The development of information technology in the shipping industry has long been established. Scada-based ship rudder control system Using the cxprogrammer and easy builder applications, is a form of innovation in the shipping sector, by utilizing PLC devices. PLC will control the ship's steering gear and then connected using a network, thus forming a Scada system. The PLC will be programmed using the cxprogrammer to control the device as needed and use the easy builder as a Graphic User Interface so that the system can be used by the crew easily through graphics and animation. The purpose of this research is to make it easier for workers on the ship to monitor and control the ship's rudder drive system and operate the Steering Gear by monitoring from the platform and engine room of the ship so that their work becomes more efficient.